Justification of the selection of renewable energy sources taking into account load schedules in conditions of uncertainty - Kryvonosov, V.; Antypov, I.; Makarevych, S.; Petrenko, A.; Kryvonosov, V.; Afinovych, S. (Energy and Automation, 2025)
One of the indicators that allows analyzing the decrease in profit is the specific value of energy costs per unit of produced product.This indicator can be both general for the enterprise and inter-departmental. It affects the increase in cost, determining the causes of quality deterioration and lack of demand, which make products uncompetitive.The increase in the value of this indicator is associated with uncertain interruptions of energy that the enterprise receives from the electric power system (EPS). The uncertainty lies both in the duration of the interruption and in its duration.The article analyzes literary sources devoted to determining the methods of selecting renewable energy sources. The most modern is the method based on probabilistic statistical data. The paper considers load schedules obtained during the study of the efficiency of the enterprise, the reliability of technical accounting, the study of electricity quality indicators and the identification of the required capacity of renewable energy sources. The introduction of the coefficient of probable power supply interruptions allows to correctly justify the choice of the RBV. The article states that determining the coefficient of probability of power supply interruption allows to clarify the capacity of renewable energy sources. Taking into account the growth of energy costs per unit of production will allow to plan the operation of the enterprise in conditions of uncertainty of outages.Key words: load schedule, renewable energy sources, probability, specific costs per unit of production